Structural insights into the mechanism of pancreatic KATP channel regulation by nucleotides - Wang, Mengmeng; Wu, Jing-Xiang; Ding, Dian; Chen, Lei (Nature communications, 2022)
ATP-sensitive potassium channels (K ATP ) are metabolic sensors that convert the intracellular ATP/ADP ratio to the excitability of cells. They are involved in many physiological processes and implicated in several human diseases. Here we present the cryo-EM structures of the pancreatic K ATP channel in both the closed state and the pre-open state, resolved in the same sample. We observe the binding of nucleotides at the inhibitory sites of the Kir6.2 channel in the closed but not in the pre-open state. Structural comparisons reveal the mechanism for ATP inhibition and Mg-ADP activation, two fundamental properties of K ATP channels. Moreover, the structures also uncover the activation mechanism of diazoxide-type K ATP openers. K ATP channels are energy sensors. Here, authors report the Cryo-EM structures of pancreatic K ATP in both the closed state and the pre-open state. These structures illuminate the mechanism of K ATP channel regulation by the intracellular nucleotides.